2021
DOI: 10.33400/kuje.913253
|View full text |Cite
|
Sign up to set email alerts
|

Examining the cyberbullying awareness levels of senior pre-service teachers: Example of Buca Faculty of Education

Abstract: Bu araştırmanın amacı, öğretmen adaylarının siber zorbalık farkındalık düzeylerini belirlemektir. Siber zorbalık farkındalık düzeyleri puan türü, bölüm, cinsiyet, siber zorbalığı duyma, siber zorbalıkla ilgili eğitim alma, günlük internet kullanımı ve anne-baba çalışma durumu açısından ele alınmıştır. Araştırmanın çalışma grubunu; 2019-2020 eğitim öğretim yılında, İzmir ili Dokuz Eylül Üniversitesi Buca Eğitim Fakültesi 4. sınıfta öğrenim gören 324'ü kadın, 147'si erkek olmak üzere 471 öğretmen adayı oluşturma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
0
0
Order By: Relevance
“…As a result, it has been determined that the cyberbullying awareness levels of primary school teachers are quite high in general. Aydın and Arslan (2021), when the numerical data of the gender variable were examined in their research, it was determined that the cyberbullying awareness levels were moderate for both male and female teachers. When the teachers' cyberbullying awareness levels were compared with their demographic characteristics and the related analyzes were evaluated; It was concluded that teachers' cyberbullying levels had a significant effect according to the gender variable and this significance was in favor of female teachers.…”
Section: Conclusion Discussion and Suggestionsmentioning
confidence: 99%
“…As a result, it has been determined that the cyberbullying awareness levels of primary school teachers are quite high in general. Aydın and Arslan (2021), when the numerical data of the gender variable were examined in their research, it was determined that the cyberbullying awareness levels were moderate for both male and female teachers. When the teachers' cyberbullying awareness levels were compared with their demographic characteristics and the related analyzes were evaluated; It was concluded that teachers' cyberbullying levels had a significant effect according to the gender variable and this significance was in favor of female teachers.…”
Section: Conclusion Discussion and Suggestionsmentioning
confidence: 99%